Transparent yellowing-resistant UV adhesive and preparation method thereof
By using epoxy resin base material and modified polytitanium silicone and other raw materials in UV glue, combined with specific preparation methods, the problems of high curing shrinkage and poor environmental aging resistance during the curing process are solved, and transparent yellowing-resistant UV glue with high optical performance and stability are achieved.
Patent Information
- Application Number
- CN202411620749.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-07
AI Technical Summary
During the curing process, existing UV glues have high curing shrinkage and poor environmental aging resistance. Especially under high temperature and humidity conditions, they are prone to performance degradation and are difficult to maintain good transparency and yellowing resistance for a long time.
A transparent yellowing-resistant UV glue is used, and the raw material components include 20 to 40 parts by mass of the epoxy resin base material, 5 to 15 parts by mass of modified polytitanium silicone, 1.5 to 2.5 parts by mass of the photoinitiator, 10 to 20 parts by mass of oxetane and 7 to 9 parts by mass of vinyl ether. The compatibility and crosslinking density of the material are improved by a specific preparation method and combination of raw materials.
It achieves the effect of small volume changes and low internal stress during the curing process, and at the same time, the material's heat resistance, UV aging resistance and yellowing resistance are improved, ensuring high optical performance and stability over a long period of time.
Smart Images

Figure BDA0005133525690000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a transparent yellowing-resistant UV adhesive and a preparation method thereof. Background Art
[0002] With the development of science and technology and the enhancement of environmental awareness, fast-curing, green, environmentally friendly and energy-saving materials are gaining more and more attention in all walks of life. As a typical light-curing material, UV glue has achieved rapid development in the bonding application of transparent materials due to its above advantages. Especially in the field of optics, UV glue is widely used, such as for bonding screen protective films, optical lens groups and optical components in various electronic devices.
[0003] However, despite the many advantages of UV glue, the presence of its main component, acrylate, also brings some problems. Acrylate-based UV glue decomposes free radicals under ultraviolet light through free radical initiators, which then initiate free radical polymerization reactions to complete the curing process. Although this process is highly efficient, it is also accompanied by a high curing shrinkage rate, that is, the internal stress generated by the reduction in volume during the curing process is large. This stress may cause deformation of the bonded object, which is a considerable challenge for products that require high-precision assembly. In addition, the environmental aging resistance of acrylate-based UV glue is relatively poor, especially under high temperature and humid conditions, and performance degradation is prone to occur, which limits its application in some special environments.
[0004] In contrast, epoxy resin, as an alternative material, has shown significant advantages in the application of UV optical adhesives. Epoxy resin can be cured through the action of cationic photoinitiators. The volume change during the whole process is small and almost no volatiles are produced. Therefore, it can maintain low internal stress after curing and reduce deformation caused by curing shrinkage. At the same time, epoxy resin also has better resistance to high temperature and wet heat aging, and can meet more stringent conditions of use. However, even so, when epoxy resin is used as UV optical adhesive, how to maintain good transparency and anti-yellowing ability during long-term environmental aging is still a problem that needs to be solved. This is especially important for applications that require long-term high optical performance.
[0005] Therefore, the present invention provides a transparent yellowing-resistant UV glue and a preparation method thereof, aiming to overcome the deficiencies in the prior art and provide a new material which retains the inherent advantages of UV glue and excels in curing shrinkage, environmental aging resistance, and especially yellowing resistance, thereby further broadening the application scope of UV glue in precision optical devices and other high-end fields. Summary of the invention
[0006] The purpose of the present invention is to provide a transparent yellowing-resistant UV adhesive and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.
[0007] The technical solution for achieving the purpose of the present invention is: a transparent yellowing-resistant UV adhesive, wherein the raw material components include, by weight: 20 to 40 parts by weight of epoxy resin base material, 5 to 15 parts by weight of modified polytitanium siloxane, 1.5 to 2.5 parts by weight of photoinitiator, 10 to 20 parts by weight of oxetane, and 7 to 9 parts by weight of vinyl ether.
[0008] Furthermore, the epoxy resin base material includes any one or a combination of at least two of bisphenol A epoxy resin YL980, hydrogenated bisphenol A epoxy resin YX-8000D, alicyclic epoxy resin celloxide 2021P, alicyclic epoxy resin Epolead GT401, and alicyclic epoxy resin S-28.
[0009] Furthermore, the epoxy resin base material includes alicyclic epoxy resin Epolead GT401.
[0010] Furthermore, the modified polytitanium siloxane is obtained by polycondensation of siloxane monomer and tetrabutyl titanate.
[0011] Furthermore, the siloxane monomer includes any one or a combination of at least two of γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, and vinylmethyldiethoxysilane.
[0012] The present invention provides a method for preparing a transparent yellowing-resistant UV adhesive, comprising the following preparation steps:
[0013] (1) Weigh the weight of each of the above raw material components;
[0014] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether are added to a reaction kettle and stirred at 48-52° C. for 18-22 minutes, and then weighed modified polytitanium siloxane is added and stirred for 18-22 minutes. The mixture is then cooled to room temperature and a photoinitiator is added to obtain a transparent yellowing-resistant UV adhesive.
[0015] Furthermore, the preparation method of the modified polytitanium siloxane is as follows: after weighing the siloxane monomer and barium hydroxide, they are put into the reactor in turn, the temperature is raised to 78-82°C under nitrogen protection, and the reaction is stirred for 3.5-4.5 hours, and the gas by-products are discharged. After vacuum drying at 58-62°C for 4.5-5.5 hours, 4-6 times the mass of the siloxane monomer solvent benzene is added, stirring is continued for 25-35 minutes, and then the temperature is reduced to 44-46°C, and a benzene solution of tetrabutyl titanate is added dropwise. After the addition is completed, the reaction is continued for 2.8-3.2 hours, and then the modified polytitanium siloxane is obtained by rotary evaporation and drying.
[0016] Furthermore, the siloxane monomer adopts γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, and vinylmethyldiethoxysilane, wherein the molar ratio of γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinylmethyldiethoxysilane and barium hydroxide is 1:0.4~0.6:0.4~0.6:0.004~0.006.
[0017] Furthermore, the molar ratio of tetrabutyl titanate to γ-glycidyloxypropylmethyldiethoxysilane in the benzene solution of tetrabutyl titanate is 0.4 to 0.6; and the mass of benzene is 4 to 6 times the mass of siloxane monomer.
[0018] Furthermore, the UV curing conditions of the transparent yellowing-resistant UV adhesive include: ultraviolet light band 250-400nm, time 10min-2h.
[0019] By adopting the above technical solution, the present invention has the following beneficial effects:
[0020] (1) The transparent anti-yellowing UV adhesive of the present invention has modified polytitanium siloxane added to its epoxy resin base material, wherein polytitanium siloxane refers to an elemental organic polymer composed of three elements: silicon, oxygen and titanium. This polymer not only inherits the excellent properties of polysiloxane, such as good flexibility and comprehensive performance that remains stable over a wide temperature range, but also further improves the heat resistance, anti-ultraviolet aging ability and anti-yellowing performance of the material due to the introduction of titanium.
[0021] (2) The epoxy resin base material of the present invention uses at least alicyclic epoxy resin Epolead GT401. Epolead GT401 has multiple epoxy functional groups, and these functional groups are distributed on multiple side chains. Such a structure not only increases the cross-linking density between molecules, but also makes the cured adhesive network stronger and more stable. The presence of multiple side chains improves the flexibility of the resin while maintaining good mechanical strength. This structure also helps to improve the heat resistance and chemical resistance of the adhesive, allowing it to be used under a wider range of environmental conditions.
[0022] (3) However, epoxy resin and polytitanium siloxane are very likely to phase separate during the mixing process, that is, they cannot be mixed evenly. This incompatibility will cause the physical properties of the mixed material, such as strength, toughness and bonding quality, to drop significantly. The present invention uses γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinylmethyldiethoxysilane as siloxane monomers to form a modified polytitanium siloxane molecular chain with a certain branched structure, and introduces polar groups such as epoxy groups to improve the problem of poor bonding effect. At the same time, after the modified polytitanium siloxane and the epoxy resin base material are interpenetrated and cross-linked, the active groups on the modified polytitanium siloxane form effective chemical bonds with the epoxy resin base material through UV curing, which not only enhances the compatibility between the two, but also improves the incompatibility between the epoxy resin base material and the polytitanium siloxane, thereby increasing the strength, toughness and bonding quality of the transparent yellowing-resistant UV adhesive. DETAILED DESCRIPTION
[0023] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0024] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0025] Some of the raw materials of some embodiments and comparative examples of the present invention are as follows:
[0026] The epoxy resin base material is obtained by mixing Mitsubishi Chemical's bisphenol A epoxy resin YL980 and hydrogenated bisphenol A epoxy resin YX-8000D and Daicel's alicyclic epoxy resin Epolead GT401 in a mass ratio of 5:5:20.
[0027] The photoinitiator used was UVI6976 from Dow Chemical.
[0028] Oxetane was prepared by mixing OXT-101 and OXT-221 synthesized from East Asia in a mass ratio of 1:2.
[0029] The vinyl ether used was DVE-2 produced by BASF.
[0030] Example 1
[0031] A method for preparing a transparent yellowing-resistant UV adhesive comprises the following steps:
[0032] (1) Weigh the weight parts of the raw material components according to claim 1: 20 parts by weight of epoxy resin base material, 5 parts by weight of modified polytitanium siloxane, 1.5 parts by weight of photoinitiator, 10 parts by weight of oxetane, and 7 parts by weight of vinyl ether;
[0033] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether were added to a reaction kettle and stirred at 48°C for 18 minutes, and then weighed modified polytitanium siloxane was added and stirred for 18 minutes. The mixture was then cooled to room temperature and a photoinitiator was added to obtain a transparent yellowing-resistant UV adhesive.
[0034] The preparation method of the modified polytitanium siloxane is as follows: after weighing the siloxane monomer and barium hydroxide, they are put into a reaction kettle in turn, the temperature is raised to 78° C. under nitrogen protection, stirred and reacted for 3.5 hours, gas by-products are discharged, and vacuum dried at 58° C. for 4.5 hours, and then solvent benzene with a mass of 4 times that of the siloxane monomer is added, and stirring is continued for 25 minutes, and then the temperature is lowered to 44° C., and a benzene solution of tetrabutyl titanate is added dropwise. After the addition is completed, the reaction is continued for 2.8 hours. The entire addition and reaction process is subjected to reduced pressure distillation, followed by rotary evaporation and drying to obtain the modified polytitanium siloxane.
[0035] Wherein: the siloxane monomers are γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, and vinylmethyldiethoxysilane, wherein the molar ratio of γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinylmethyldiethoxysilane, and barium hydroxide is 1:0.4:0.4:0.004; the molar ratio of tetrabutyl titanate to γ-glycidyloxypropylmethyldiethoxysilane in the benzene solution of tetrabutyl titanate is 0.4; and the mass of benzene is 4 times the mass of the siloxane monomers.
[0036] Example 2
[0037] A method for preparing a transparent yellowing-resistant UV adhesive comprises the following steps:
[0038] (1) Weigh the weight parts of the raw material components according to claim 1: 30 parts by weight of epoxy resin base material, 10 parts by weight of modified polytitanium siloxane, 2 parts by weight of photoinitiator, 15 parts by weight of oxetane, and 8 parts by weight of vinyl ether;
[0039] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether were added to a reaction kettle and stirred at 50° C. for 20 min. Then weighed modified polytitanium siloxane was added and stirred for 20 min. The mixture was then cooled to room temperature and a photoinitiator was added to obtain a transparent yellowing-resistant UV adhesive.
[0040] The preparation method of the modified polytitanium siloxane is as follows: after weighing the siloxane monomer and barium hydroxide, they are put into a reaction kettle in turn, the temperature is raised to 80° C. under nitrogen protection, stirred and reacted for 4 hours, the gas by-products are discharged, and vacuum dried at 60° C. for 5 hours, and then solvent benzene with a mass 5 times that of the siloxane monomer is added, and stirring is continued for 30 minutes, and then the temperature is lowered to 45° C., and a benzene solution of tetrabutyl titanate is added dropwise. After the addition is completed, the reaction is continued for 3 hours. The entire addition and reaction process must be subjected to reduced pressure distillation, followed by rotary evaporation and drying to obtain the modified polytitanium siloxane.
[0041] Wherein: the siloxane monomers are γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, and vinylmethyldiethoxysilane, wherein the molar ratio of γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinylmethyldiethoxysilane, and barium hydroxide is 1:0.5:0.5:0.005; the molar ratio of tetrabutyl titanate to γ-glycidyloxypropylmethyldiethoxysilane in the benzene solution of tetrabutyl titanate is 0.5; and the mass of benzene is 5 times the mass of the siloxane monomers.
[0042] Example 3
[0043] A method for preparing a transparent yellowing-resistant UV adhesive comprises the following steps:
[0044] (1) Weigh the raw material components according to claim 1 in parts by weight: 40 parts by weight of epoxy resin base material, 15 parts by weight of modified polytitanium siloxane, 2.5 parts by weight of photoinitiator, 20 parts by weight of oxetane, and 9 parts by weight of vinyl ether;
[0045] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether were added to a reaction kettle and stirred at 52° C. for 22 minutes. Then weighed modified polytitanium siloxane was added and stirred for 22 minutes. The mixture was then cooled to room temperature and a photoinitiator was added to obtain a transparent yellowing-resistant UV adhesive.
[0046] The preparation method of the modified polytitanium siloxane is as follows: after weighing the siloxane monomer and barium hydroxide, they are put into a reaction kettle in turn, the temperature is raised to 82° C. under nitrogen protection, stirred and reacted for 4.5 hours, gas by-products are discharged, and vacuum dried at 62° C. for 5.5 hours, and then solvent benzene with a mass of 6 times that of the siloxane monomer is added, and stirring is continued for 35 minutes, and then the temperature is lowered to 46° C., and a benzene solution of tetrabutyl titanate is added dropwise. The entire dropwise addition and reaction process is subjected to reduced pressure distillation. After the dropwise addition is completed, the reaction is continued for 3.2 hours, and then the modified polytitanium siloxane is obtained by rotary evaporation and drying.
[0047] Wherein: the siloxane monomers are γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, and vinylmethyldiethoxysilane, wherein the molar ratio of γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinylmethyldiethoxysilane, and barium hydroxide is 1:0.6:0.6:0.006; the molar ratio of tetrabutyl titanate to γ-glycidyloxypropylmethyldiethoxysilane in the benzene solution of tetrabutyl titanate is 0.6; and the mass of benzene is 6 times the mass of the siloxane monomers.
[0048] Comparative Example 1
[0049] The difference between Comparative Example 1 and Example 2 is that the raw material components of the transparent yellowing-resistant UV adhesive only use epoxy resin base material, epoxy polysiloxane, photoinitiator, oxetane, and vinyl ether. The specific preparation steps are as follows:
[0050] A method for preparing a transparent yellowing-resistant UV adhesive comprises the following steps:
[0051] (1) Weigh the weight parts of the raw material components according to claim 1: 30 parts by weight of epoxy resin base material, 10 parts by weight of epoxy polysiloxane, 2 parts by weight of photoinitiator, 15 parts by weight of oxetane, and 8 parts by weight of vinyl ether;
[0052] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether were added to a reaction kettle and stirred at 50° C. for 20 min. Then weighed modified polytitanium siloxane was added and stirred for 20 min. The mixture was then cooled to room temperature and a photoinitiator was added to obtain a transparent yellowing-resistant UV adhesive.
[0053] The epoxy polysiloxane used is IOTA 105 produced by Anhui IOTA Silicone Oil Co., Ltd.
[0054] Comparative Example 2
[0055] The difference between Comparative Example 2 and Example 2 is that the siloxane monomers are γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, and vinylmethyldiethoxysilane. The specific preparation steps are as follows:
[0056] A method for preparing a transparent yellowing-resistant UV adhesive comprises the following steps:
[0057] (1) Weigh the weight parts of the raw material components according to claim 1: 30 parts by weight of epoxy resin base material, 10 parts by weight of modified polytitanium siloxane, 2 parts by weight of photoinitiator, 15 parts by weight of oxetane, and 8 parts by weight of vinyl ether;
[0058] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether were added to a reaction kettle and stirred at 50° C. for 20 min. Then weighed modified polytitanium siloxane was added and stirred for 20 min. The mixture was then cooled to room temperature and a photoinitiator was added to obtain a transparent yellowing-resistant UV adhesive.
[0059] The preparation method of the modified polytitanium siloxane is as follows: after weighing the siloxane monomer and barium hydroxide, they are put into a reaction kettle in turn, the temperature is raised to 80° C. under nitrogen protection, stirred and reacted for 4 hours, the gas by-products are discharged, and vacuum dried at 60° C. for 5 hours, and then solvent benzene with a mass 5 times that of the siloxane monomer is added, and stirring is continued for 30 minutes, and then the temperature is lowered to 45° C., and a benzene solution of tetrabutyl titanate is added dropwise. After the addition is completed, the reaction is continued for 3 hours. The entire addition and reaction process must be subjected to reduced pressure distillation, followed by rotary evaporation and drying to obtain the modified polytitanium siloxane.
[0060] Wherein: the siloxane monomer uses γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, and vinylmethyldiethoxysilane, wherein the molar ratio of γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, vinylmethyldiethoxysilane, and barium hydroxide is 1:0.5:0.5:0.005; the molar ratio of tetrabutyl titanate to γ-glycidyloxypropyl trimethoxysilane in the benzene solution of tetrabutyl titanate is 0.5; and the mass of benzene is 5 times the mass of the siloxane monomer.
[0061] Comparative Example 3
[0062] The difference between Comparative Example 3 and Example 2 is that the modified polytitanium siloxane is a mixture of hydroxyl-terminated polydimethylsiloxane and tetrabutyl titanate, and the specific preparation steps are as follows:
[0063] A method for preparing a transparent yellowing-resistant UV adhesive comprises the following steps:
[0064] (1) Weigh the weight parts of the raw material components according to claim 1: 30 parts by weight of epoxy resin base material, 10 parts by weight of modified polytitanium siloxane, 2 parts by weight of photoinitiator, 15 parts by weight of oxetane, and 8 parts by weight of vinyl ether;
[0065] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether were added to a reaction kettle and stirred at 50° C. for 20 min. Then weighed modified polytitanium siloxane was added and stirred for 20 min. The mixture was then cooled to room temperature and a photoinitiator was added to obtain a transparent yellowing-resistant UV adhesive.
[0066] The preparation method of the modified polytitanium siloxane is as follows: add hydroxyl-terminated polydimethylsiloxane to solvent benzene with a mass 5 times that of the polydimethylsiloxane, stir for 30 minutes, then add tetrabutyl titanate benzene solution dropwise, continue to react for 3 hours after the addition is complete, and perform reduced pressure distillation throughout the entire addition and reaction process, followed by rotary evaporation and drying to obtain the modified polytitanium siloxane.
[0067] Wherein: the molar ratio of tetrabutyl titanate to hydroxyl-terminated polydimethylsiloxane in the benzene solution of tetrabutyl titanate is 0.5; and the mass of benzene is 5 times the mass of hydroxyl-terminated polydimethylsiloxane.
[0068] Comparative Example 4
[0069] The difference between Comparative Example 4 and Example 2 is that the raw material components of the transparent yellowing-resistant UV adhesive only use epoxy resin base material, photoinitiator, oxetane, and vinyl ether. The specific preparation steps are as follows:
[0070] A method for preparing a transparent yellowing-resistant UV adhesive comprises the following steps:
[0071] (1) Weigh the raw material components according to claim 1 in parts by weight: 40 parts by weight of epoxy resin base material, 2 parts by weight of photoinitiator, 15 parts by weight of oxetane, and 8 parts by weight of vinyl ether;
[0072] (2) Under nitrogen protection, weighed epoxy resin base material, oxetane, and vinyl ether were added to a reaction kettle and stirred at 50° C. for 20 min. Then weighed modified polytitanium siloxane was added and stirred for 20 min. The mixture was then cooled to room temperature and a photoinitiator was added to obtain a transparent yellowing-resistant UV adhesive.
[0073] Effect example
[0074] The transparent yellowing-resistant UV glue obtained in the embodiment and the comparative example was placed in an ultraviolet aging box with a wavelength of 313 nm, taken out after 7 days, and the yellowness index was tested using a spectrophotometer. The larger the yellowness index, the more serious the yellowing.
[0075] Table 1 below shows the performance test results of the transparent yellowing-resistant UV adhesive prepared in the examples and comparative examples:
[0076] Table 1
[0077]
[0078] The data in Table 1 show that the transparent yellowing-resistant UV adhesive prepared by the present invention has a transmittance of about 96% at 400-700 nm, has a small attenuation after double 85 aging, and has good yellowing resistance and mechanical properties.
[0079] Compared with Example 2, the main difference between Comparative Example 1 and Example 2 is that different polysiloxanes are used. Comparative Example 1 uses epoxy polysiloxane (IOTA 105), while Example 2 uses modified polytitanium siloxane; since titanium is introduced into the modified polytitanium siloxane, this not only improves the heat resistance and UV aging resistance of the material, but also improves the compatibility with the epoxy resin base material by introducing polar groups such as epoxy groups, thereby enhancing the interaction between the two. Therefore, in terms of light transmittance and yellowing index, the performance of Example 2 is better than that of Comparative Example 1; and the chemical bonding formed after the interpenetration and crosslinking of the modified polytitanium siloxane and the epoxy resin base material makes Example 2 also perform better in tensile shear strength and peel strength.
[0080] Compared with Example 2, the main difference between Comparative Example 2 and Example 2 is the different selection of siloxane monomers; Comparative Example 2 uses γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinylmethyldiethoxysilane, while Example 2 uses γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinylmethyldiethoxysilane; Comparative Example 2 has a higher degree of crosslinking than Example 2, and weaker tensile properties and peel strength.
[0081] Compared with Example 2, Comparative Example 3 adopts a method of mixing hydroxyl-terminated polydimethylsiloxane with tetrabutyl titanate, while Example 2 obtains modified polytitanium siloxane by reacting specific siloxane monomers with tetrabutyl titanate, introduces polar groups, increases the adhesion and compatibility of the modified polytitanium siloxane with the base material, and Example 2 is superior to Comparative Example 3 in terms of light transmittance, yellowing index, tensile shear strength and peel strength.
[0082] Compared with Example 2, Comparative Example 4 does not add modified polytitanium siloxane, and only uses epoxy resin base material, photoinitiator, oxetane and vinyl ether, while Example 2 adds modified polytitanium siloxane, which not only improves the heat resistance and UV aging resistance of the material, but also improves the compatibility with the epoxy resin base material by introducing polar groups such as epoxy groups, thereby enhancing the comprehensive performance of the transparent yellowing-resistant UV glue. Therefore, Example 2 is superior to Comparative Example 4 in terms of light transmittance, yellowing index, tensile shear strength and peel strength.
[0083] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A transparent yellowing-resistant UV adhesive, characterized in that: The raw material components include, by weight: 20 to 40 parts by weight of epoxy resin base material, 5 to 15 parts by weight of modified polytitanium siloxane, 1.5 to 2.5 parts by weight of photoinitiator, 10 to 20 parts by weight of oxetane, and 7 to 9 parts by weight of vinyl ether.
2. The transparent yellowing-resistant UV adhesive according to claim 1, characterized in that: The epoxy resin base material includes any one of bisphenol A epoxy resin YL980, hydrogenated bisphenol A epoxy resin YX-8000D, alicyclic epoxy resin celloxide 2021P, alicyclic epoxy resin Epolead GT401, and alicyclic epoxy resin S-28, or a combination of at least two of them.
3. The transparent yellowing-resistant UV adhesive according to claim 2, characterized in that: The epoxy resin base material includes alicyclic epoxy resin Epolead GT401.
4. The transparent yellowing-resistant UV adhesive according to claim 2, characterized in that: The modified polytitanium siloxane is obtained by polycondensation of siloxane monomer and tetrabutyl titanate.
5. The transparent yellowing-resistant UV adhesive according to claim 2, characterized in that: The siloxane monomer includes any one of γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinylmethyldiethoxysilane or a combination of at least two thereof.
6. A method for preparing a transparent yellowing-resistant UV adhesive, characterized in that: The method comprises the following preparation steps: (1) Weighing the weight proportions of each raw material component according to claim 1; (2) Under nitrogen protection, weighed epoxy resin base material, oxetane and vinyl ether are added to the reaction kettle and stirred at 48-52°C for 18-22 minutes. Then weighed modified polytitanium siloxane is added and stirred for 18-22 minutes. Then the temperature is cooled to room temperature and a photoinitiator is added to obtain a transparent yellowing-resistant UV adhesive.
7. The method for preparing the transparent yellowing-resistant UV adhesive according to claim 6, characterized in that: The preparation method of the modified polytitanium siloxane is as follows: after weighing the siloxane monomer and barium hydroxide, they are put into a reaction kettle in sequence, the temperature is raised to 78-82° C. under nitrogen protection, and the mixture is stirred for reaction for 3.5-4.5 hours, gas by-products are discharged, and the mixture is vacuum dried at 58-62° C. for 4.5-5.5 hours, and then solvent benzene with a mass 4-6 times that of the siloxane monomer is added, and stirring is continued for 25-35 minutes, and then the temperature is lowered to 44-46° C., and a benzene solution of tetrabutyl titanate is added dropwise, and the reaction is continued for 2.8-3.2 hours after the addition is completed, and then the modified polytitanium siloxane is obtained by rotary evaporation and drying.
8. The method for preparing the transparent yellowing-resistant UV adhesive according to claim 7, characterized in that: The siloxane monomers are γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinylmethyldiethoxysilane, wherein the molar ratio of γ-glycidyloxypropylmethyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinylmethyldiethoxysilane and barium hydroxide is 1:0.4-0.6:0.4-0.6:0.004-0.
006.
9. The method for preparing the transparent yellowing-resistant UV adhesive according to claim 7, characterized in that: The molar ratio of tetrabutyl titanate to γ-glycidyloxypropylmethyldiethoxysilane in the benzene solution of tetrabutyl titanate is 0.4-0.6; the mass of benzene is 4-6 times the mass of siloxane monomer.
10. The method for preparing the transparent yellowing-resistant UV adhesive according to claim 6, characterized in that: The UV curing conditions of the transparent yellowing-resistant UV adhesive include: ultraviolet light band 250-400nm, time 10min-2h.